PD-1 blockade combined with gemcitabine plus nab-paclitaxel is superior to chemotherapy alone in the management of unresectable stage III/IV pancreatic cancer: a retrospective real-world study - Cheng, Daoan; Hu, Jing; Wu, Xiaoyu; Wang, Banglu; Chen, Rui; Zhao, Weiqing; Fang, Cheng; Ji, Mei (Frontiers in Oncology, 2023)
Background: Pancreatic cancer (PC) is widely recognized as one of the most malignant forms of cancer worldwide. Monotherapy with immune checkpoint inhibitors (ICI) has shown limited efficacy in treating this disease. There was controversy surrounding whether combining ICI with chemotherapy provided superior outcomes compared to chemotherapy alone. Methods: In this study, patients diagnosed with unresectable stage III/IV pancreatic cancer (PC) were classified as receiving programmed cell death protein 1 (PD-1) blockade plus gemcitabine and nab-paclitaxel (AG regimen) (PD-1/chemo, n=27, 50.9%) or chemotherapy alone (chemo, n=26, 49.1%) arm. The primary study endpoints included progression-free survival (PFS) and overall survival (OS), with an additional assessment of treatment-related adverse events graded as three or higher. Chi-square (χ2) statistics were employed to analyze the clinical differences between the two groups, while Kaplan-Meier curves were used to assess the difference in PFS. Statistical significance was defined as P-values less than 0.05 (P < 0.05). Results: The median follow-up duration was 22 months (range 1-28 months). In the PD-1/chemo arm, the median PFS was eight months, whereas it was 3.5 months in the chemo arm (HR=0.459, 95% CI: 0.252-0.846, P=0.002). Furthermore, the median OS was 15 months in the PD-1/chemo arm and eight months in the chemo arm (HR=0.345, 95% CI: 0.183-0.653, P<0.001). Within the PD-1/chemo arm, 15 (55.6%) patients experienced grade 3 treatment-related adverse events, compared to 13 (50.0%) patients in the chemo arm. Conclusions: PD-1 blockade combined with nab-paclitaxel plus gemcitabine demonstrated superior efficacy to chemotherapy alone for unresectable stage III/IV PC patients. Future studies were warranted to identify immunosensitive patient subgroups within the PC population, ultimately leading to the development of more efficacious therapeutic strategies.